Youtuber: o produtor de conteúdo do Youtube e suas práticas de produção audiovisual - Leite, Rafaela Bernardazzi Torrens (2019)
Through this study, we explore the production of video on the YouTube site and analyze how the practices of producers and consumers of audiovisual content are established based on the participation of users in the network. In this way, the goal of the research is to understand how to construct a YouTuber and its practices in the process of producing the material published on the site. Through the research we observed the path of the producers of content - PC Siqueira (channel MasPoxaVida), Kéfera Buchmann (channel 5incoMinutos), Luba (channel LubaTV), Whindersson Nunes (channel WhinderssonNunes) and Jout Jout (channel JoutJoutPrazer) - presenting the visual characteristics selected videos for analysis. For that, 14 videos from each channel on YouTube were selected between 2014 and 2018, totaling 70 videos analyzed. Among the results obtained is the identification of YouTuber's relations with its audience and the interference that it causes in the creation process, in addition to the practices related to the production of the content, whether related to the type of content itself or to the technical production of the material audio-visual. The thesis presents notes on this material, listing the main visual characteristics and practices adopted by YouTubers in the creation of the contents published on the platform. The research presents the confirmation of the hypothesis that there are recurring features in both the production practices and the content of the videos published on YouTube, using as a scope the YouTubers selected for the research. In this way, contentrelated elements such as videos with frame-like format with specific themes, use of action buttons in the film frame and call to user interaction, characters in the channel narrative, external appearances in channel videos, advertising campaigns, products of the YouTubers, relation with the brands, are characteristics that mark the construction of this producer of content as an individual that establish strategies of engagement and conversation with consuming users. Still within the scope of recurrent characteristics in the channels, the research points to elements that mark the language developed throughout the productions of YouTubers. These are practices such as the realization of the production of audiovisual content in a residential environment, low prices in the technical part of audiovisual production, talks about the YouTuber aimed at the camera, editing and editing the video, applying external image content together with content video and use of visual effects. Thus the thesis, through the analysis and interpretation of the material, points to emerging issues about the material published on YouTube. The research results confirm the hypothesis that in the production of audiovisual content on YouTube in Brazil, there are recurring characteristics both in the production practices and in the content of the videos published in the channels of the selected YouTubers.